Does drought stress always negatively affect the yield and quality of soybean in Hungary? - Basal, Oqba; Szabó, András (Acta Agraria Debreceniensis, 2019)
Globally-fluctuating climate imposed serious abiotic stresses on the agricultural sector, leading to noticeable, and sometimes disastrous, losses in yields and/or quality of crops; however, in certain cases, plants could survive stress with relatively low reductions, and sometimes even with some enhancements as a reaction to changed environment, especially in the case of mild stress. An experiment was conducted in 2017 and 2018 in Debrecen, Hungary to evaluate the mild drought stress influence on the yield and quality of three soybean cultivars. The results showed that both ES Pallador and Pedro cultivars could achieve more yield when subjected to mild drought conditions; however, protein concentration was enhanced in ES Pallador whereas slightly degraded in Pedro under drought. The cultivar Pannonia Kincse followed different trend; both yield and protein concentration were reduced under drought. Oil concentration of the three cultivars did not show significant changes; however, it always followed opposite trend to that of protein concentration. It could be concluded that both ES Pallador and Pedro are recommended to be grown under rain fed conditions in Debrecen, whereas Pannonia Kincse is recommended under irrigation conditions.